(3COH GdcGJHs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3Jedjc bOje hYdi ghGeTgG JYdjbGJ s
(3BNQgG (B:s
(3bGdhG(B: (3JaGhJ GdCeQ JbGhJkG hjLF eUOQ EaJdYJ Ydi EaJYGd, EbJJdfG EbJJGdG hPdc ef HGH eUGOQ HfGJ GdCQHYI s
(3GdfSNI HgG MhGTs
(3ChdgG Jedjc bOjes
(3fSNI NGeSI ajgG VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B15 s
Keywords: (3GdCOHs